Performance analysis and diagnosis of steam power plant using real time expert system - Wong, Chee Beng. (2009)
Research into the development of a prototype real-time expert system for performance analysis and diagnosis of a 250 MW steam power plant is described. This research effort resulted in the creation of a prototype expert system that enables certain abnormal or inefficient operating conditions such as incomplete combustion and high exhaust gas temperature to be detected or simulated, analysed and diagnosed. The prototype expert system also provides a graphical display of the power plant, models important electrical, thermal and mechanical parameters and determines the performance of the steam plant by evaluating the boiler and turbine efficiency based on ASME/ANSI performance test code.